Comparative analysis of maxillary expansion techniques using orthodontic appliances - L. A. Kozhevnikova; G D. Dzhabrailova; S. M. Abdulkerimova; K. N. Kerimova; O. V. Pilshchikova; V. M. Slonova; A. А. Gevorkyan (LLC "Endo Press", 2020)
Palatal dilation techniques were developed as a method of applying significant force to the upper jaw in a horizontal plane to rupture the median palatal suture. To achieve this goal, various designs of devices have been developed over the years. The subject of the study of many authors were changes in the bone and dental system, as well as the duration of treatment results obtained due to the use of functional devices with different rates of action. The rate of expansion depends on the level of applied forces and the mode of activation of the device. There are 3 rates of expansion of the upper jaw: slow, semi-rapid and rapid. An alternative to rapid palatal expansion with the activation of the screw 1-2 times a day is a slow expansion with the activation of the screw 1 every 2 days or using of another type of apparatus, where the source of activation is the spring. The study, which compared the device with a spring and the device for rapid palatal expansion of adolescents, showed that they have a similar effect. The available data indicate that histological examination of sutures after palatal dilation confirmed the presence of pronounced activity of both apposition and resorption [25,26]. Devices for rapid palatal expansion (RPE/RME-rapid palatal/maxillary expansion), as well as semi-rapid and slow expansion are traditionally used as a method of correction of cross bite. In addition, they are used to increase the perimeter of the dentition of the upper jaw, normalize the level of the Wilson curve, "expand the smile" and to increase the patency of the respiratory tract. Maxillofacial anatomy is a critical factor influencing the pathophysiology of obstructive sleep apnea. In combination with decreased oral volume, transverse maxillary deficiency is known to be a key contributor to obstructive sleep apnoe. After GNE, there is an increase in the volume of the nasal cavity and a decrease in the resistance of the nasal airflow. RME also allows the tongue to protrude forward and upward, expanding the space of the posterior pharyngeal airway during sleep [31, 32]. With regard to the pathology of the bite, the cross bite is much more common because of the narrow upper jaw than because of the insufficient width of the lower jaw. The most popular way to treat this pathology is rapid expansion of the jaw (RME).